Snowball Throwing Method as an Effort to Improve Dental Health Knowledge in Elementary School Students - Nasita, Putri Aprilina; Purnama, Tedi (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Individual awareness of dental and oral health is essential in preventing dental health problems, therefore dental health education needs to be improved. Good knowledge correlates with greater attention to dental health, making dental health counseling an important step in educating children. The success of counseling can be influenced by the methods and tools used; thus, engaging learning methods such as snowball throwing can enhance students’ activeness and interest in learning. This method has been proven effective in educating students to improve dental health. Objective: To analyze the effectiveness dental health knowledge before and after education using the snowball throwing method. Method: This study was conducted using a pre-experimental method with one group pretest posttest design. This study was conducted at SDN Depok 5. The sampling technique used a total sampling of 36 students. Independent variables: education using the snowball throwing method and dependent variables: students' level of knowledge of dental health. The instruments used were questionnaires and questions in snowball throwing. Data analysis was tested using the paired sample t-test. Results: This study showed that the mean knowledge of dental health before education using snowball throwing was 43.70 and after education using snowball throwing was 72.96 with the results of the paired sample t-test obtained a p-value of p <0.000. Conclusion: The snowball throwing method is effective in improving fifth-grade students' knowledge of dental health.